Attitudes and Perceptions to Prehabilitation in Lung Cancer. (May 2020) - Shukla, Anna; Granger, Catherine L.; Wright, Gavin M.; Edbrooke, Lara; Denehy, Linda
Background: Prehabilitation to maximize exercise capacity before lung cancer surgery has the potential to improve operative tolerability and patient outcomes. However, translation of this evidence into clinical practice is limited.Aims: To determine the acceptability and perceived benefit of prehabilitation in lung cancer among thoracic surgeons.Procedure: 198 cardiothoracic surgeons within Australia and New Zealand were surveyed to evaluate their attitudes and perceived benefits of prehabilitation in lung cancer.Results: Response rate was 14%. A moderate proportion of respondents reported that there is a need to refer lung resection patients to preoperative physiotherapy/prehabilitation, particularly high-risk patients or those with borderline fitness for surgery. 91% of surgeons were willing to delay surgery (as indicated by cancer stage/type) to optimize patients via prehabilitation. The main barriers to prehabilitation reported were patient comorbidities and access to allied health professionals, with 33% stating that they were unsure who to refer to for prehabilitation in thoracic surgery. This is despite 60% of the cohort reporting that pulmonary rehabilitation is available as a preoperative resource. 92% of respondents believe that further research into prehabilitation in lung cancer is warranted.Conclusion: The benefits of prehabilitation for the oncology population have been well documented in the literature over recent years and this is reflected in the perceptions surgeons had on the benefits of prehabilitation for their patients. This survey demonstrates an interest among cardiothoracic surgeons in favor of prehabilitation, and therefore further research and demonstration of its benefit is needed in lung cancer to facilitate implementation into practice.